Use of STAT-Flame AAS for the Determination of Lead and Cadmium Pollution in Urban Center - Karaaslan, Nagihan M.; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2011)
Lead (Pb) and cadmium (Cd) concentrations in Pinus Nigra L., Cedrus Libani, and Cupressus Arizonica plants were determined for biomonitoring of environmental pollution in Elazig, Turkey. For this purpose, leaves from these plant species together with soil samples were collected from various locations during different months of the year. The samples were digested using the dry ashing method. For the determinations, an on-line method was applied using slotted tube atom trap-flame atomic absorption spectrometry (STAT-FAAS) which is fast, involves low risk of contamination, and low cost. The results obtained were evaluated based on traffic density, industrial factories, population, and seasonal variation. Lead and Cd concentrations were found to range from 139 to 768 mu g kg(-1) and
Keywords: Trace-Metal Concentrations; Elements; Leaves; Biomonitors; Copper; Enrichment; Health; Plants; Soil